Evaluation of a New Mordant Based Haematoxylin Dye (Haematoxylin X) for Use in Clinical Pathology - J. A. Gabriel; C. D'Amico; U. Kosgodage; J. Satoc; N. Haine; S. Willis; G. E. Orchard (Frontiers Media S.A., 2023)
Recently, St John's Dermatopathology Laboratory and CellPath Ltd have developed a new patented haematoxylin dye (Haematoxylin X) that utilises a chromium-based mordant (Chromium Sulphate). In this study, the performance of this new haematoxylin (Haematoxylin X) was compared against some commonly utilised alum-based haematoxylins (Carazzi's, Harris' and Mayer's) when used as a part of formalin-fixed paraffin embedded (FFPE) tissue, special stains, immunohistochemical counterstaining and frozen section (Mohs procedure) staining procedures. FFPE sections of different tissue types and frozen skin tissues were sectioned and stained with each haematoxylin subtype to allow for a direct comparison of staining quality. The slides were independently evaluated microscopically by two assessors. A combined score was generated to determine the sensitivity (defined as the intensity of haematoxylin staining being too weak or too strong and the colour of the haematoxylin staining not being blue/black) and specificity (defined as the presence of haematoxylin background staining, uneven staining, and staining deposits) for each of the four haematoxylin subtypes. The scoring criteria were based on the UKNEQAS Cellular pathology techniques assessment criteria. In FFPE tissue, the results for specificity identified Harris haematoxylin scoring the highest (91.2%) followed by Haematoxylin X (88.0%) and Mayer's (87.0%). The sensitivity scores again identified Harris haematoxylin as scoring the highest (95.1%) followed by Haematoxylin X (90.0%) and Mayer's (88.0%). In frozen tissue, the results for specificity identified Haematoxylin X as scoring the highest (85.5%) followed by Carazzi's (80.7%) and Harris' (77.4%). The sensitivity scores again identified Haematoxylin X as scoring the highest (86.8%) followed by Carazzi's (82.0%) and Harris' (81.0%). The results achieved with all four haematoxylins showed a high degree of comparability, with Harris' haematoxylin scoring high scores overall compared to the other four when assessing FFPE sections. This may have been due to familiarity with the use of Harris' haematoxylin in-house. There was also evidence of more pronounced staining of extracellular mucin proteins with Haematoxylin X compared to the other alum haematoxylins that were assessed. Haematoxylin X scored highest when used in frozen section staining. In addition, Haematoxylin X has a potential applications for use in IHC and special stains procedures as a counterstain.